Identification of Aspergillus Sp. on Sputum Patient Suspect Tuberculosis at Salotungo Public Health Center of Soppeng Regency - Naim, Nurlia (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Fungal infections not only occur in the sidelines of the hands, feet or skin but can also infect organs with mycotoxins produced and are carcinogenic. Aspergillus sp can spread through the air and is an opportunistic infection after the lung perforation due to Mycobacterium tuberculosis, and if not handled properly can cause death. The purpose of this research is to know the existence of Aspergilus sp on sputum patient suspect tuberculosis at Salotungo Public Health Center of Soppeng Regency. The type of this research is observational laboratory with culture and microscopic method. The sample selection was done by accidental sampling technique. Based on the results of this study it was concluded that Aspergilus sp found in suspect tuberculosis patients in Salotungo Public Health Center of Soppeng District, so it is advisable to conduct a deep identification process to determine the specific fungal species that infect tuberculosis patients